2021
DOI: 10.1063/5.0071757
|View full text |Cite
|
Sign up to set email alerts
|

Efficient geometrical control of spin waves in microscopic YIG waveguides

Abstract: We study, experimentally and by micromagnetic simulations, the propagation of spin waves in 100-nm thick YIG waveguides, where the width linearly decreases from 2 to 0.5 μm over a transition region with varying lengths between 2.5 and 10 μm. We show that this geometry results in a downconversion of the wavelength, enabling efficient generation of waves with wavelengths down to 350 nm. We also find that this geometry leads to a modification in the group velocity, allowing for almost-dispersionless propagation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…To make the effect more prominent at smaller distances, it is possible to use magnonic crystals, multilayered structures, or their hybrids [43][44][45] with a high dispersion of the group velocity of SWs. On the flipside, the geometrical design of the waveguide paves the way to suppress the dispersion altogether 46,47 .…”
Section: Please Cite This Article Asmentioning
confidence: 99%
“…To make the effect more prominent at smaller distances, it is possible to use magnonic crystals, multilayered structures, or their hybrids [43][44][45] with a high dispersion of the group velocity of SWs. On the flipside, the geometrical design of the waveguide paves the way to suppress the dispersion altogether 46,47 .…”
Section: Please Cite This Article Asmentioning
confidence: 99%
“…Up to now, the standard experimental approach has involved the use of elongated SW waveguides, usually with canted ends [27,28,35,36]. Moreover, a recent study showed that the SW intensity is well maintained in nanoscopic, tapered waveguides [37]. Following further miniaturization and an increased packing of SW devices, controlled SW damping will become important in limiting back reflection at open-ended or unused waveguide ports.…”
Section: Introductionmentioning
confidence: 99%